2000
DOI: 10.1116/1.582402
|View full text |Cite
|
Sign up to set email alerts
|

Phase development of radio-frequency magnetron sputter-deposited Pb(Mg1/3Nb2/3)O3–PbTiO3 (90/10) thin films

Abstract: Pb(Mg 1/3 Nb 2/3 )O 3 –PbTiO 3 (PMN–PT) films were deposited by the radio-frequency magnetron sputtering technique with Pb- and Mg-enriched ceramic targets. The perovskite structural growth was carried out over a wide range of processing parameters. PMN–PT targets were synthesized by the columbite technique. Surface cracking was due to the residual stress induced by low-temperature deposition. To reduce the surface-layer delamination, the substrate temperature during deposition was increased to 500 °C. Even th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…However, previous results (Hoffmann et al, 2002;Zhou et al, 2002;Gong et al, 2004;Donnely et al, 2003) had shown that crystallization temperature was usually higher than 600 • C. Many techniques have been attempted to prepare PMN-PT films, such as the sol-gel method (Hoffmann et al, 2002;Zhou et al, 2002;Gong et al, 2004), pulsed laser deposition (PLD) (Donnely et al, 2003;Lala et al, 2004;Ho et al, 2004), metal organic chemical vapor deposition (MOCVD) (Takeshima et al, 1995;Lee et al, 2001), and 0924-0136/$ -see front matter © 2008 Elsevier B.V. All rights reserved. doi:10.1016/j.jmatprotec.2008.02.003 radio frequency magnetron sputtering (RF-magnetron sputtering) (Lee et al, 2000;Li et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, previous results (Hoffmann et al, 2002;Zhou et al, 2002;Gong et al, 2004;Donnely et al, 2003) had shown that crystallization temperature was usually higher than 600 • C. Many techniques have been attempted to prepare PMN-PT films, such as the sol-gel method (Hoffmann et al, 2002;Zhou et al, 2002;Gong et al, 2004), pulsed laser deposition (PLD) (Donnely et al, 2003;Lala et al, 2004;Ho et al, 2004), metal organic chemical vapor deposition (MOCVD) (Takeshima et al, 1995;Lee et al, 2001), and 0924-0136/$ -see front matter © 2008 Elsevier B.V. All rights reserved. doi:10.1016/j.jmatprotec.2008.02.003 radio frequency magnetron sputtering (RF-magnetron sputtering) (Lee et al, 2000;Li et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The interest in thin film is due to the growing need for miniaturized electromechanical actuators, transducers, and sensors in many fields of science and technology. Various fabrication methods are used for present day ferroelectric thin film fabrication, amongst which is a sol-gel method that appears to have one of the highest possibilities of controlling the stoichiometric composition.…”
Section: Introductionmentioning
confidence: 99%
“…With this in mind, we have prepared PMN-PZ-PT thin films through a sol-gel process, employing different annealing temperatures that have been optimized based on detailed structural and electrical characterizations. 5 ] were dissolved in 2-ethoxyethanol at room temperature. Finally the above two precursor solutions were mixed and refluxed for 3 h, which yielded clear sol.…”
Section: Introductionmentioning
confidence: 99%
“…5 There are several reports concerning the deposition and characterization of PMN-PT thin films. Deposition techniques reported include pulsed laser deposition, 6 -8 sol-gel processing, 9,10 rf sputtering, 11 and metal-organic chemical vapor deposition. 12 These publications describe the electric properties of PMN-PT films polarized through the thickness.…”
Section: Introductionmentioning
confidence: 99%